PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DI KELAS INTERNASIONAL INSTITUT PESANTREN KH. ABDUL CHALIM - Mokhammad Nizzam (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
The present study aims to describe BIPA program held at Institut Pesantren KH. Abdul Chalim, covering the planning, implementation and problems. Using descriptive qualitative design, the data analysis shows that communicative approach is deployed on the instructional process. The emerging problems include linguistic, cultural and facility aspects. Not only the instructors, but also stake-holders need to actively work on the solutions.